If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7t + -25 = -1 + 3t Reorder the terms: -25 + 7t = -1 + 3t Solving -25 + 7t = -1 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -25 + 7t + -3t = -1 + 3t + -3t Combine like terms: 7t + -3t = 4t -25 + 4t = -1 + 3t + -3t Combine like terms: 3t + -3t = 0 -25 + 4t = -1 + 0 -25 + 4t = -1 Add '25' to each side of the equation. -25 + 25 + 4t = -1 + 25 Combine like terms: -25 + 25 = 0 0 + 4t = -1 + 25 4t = -1 + 25 Combine like terms: -1 + 25 = 24 4t = 24 Divide each side by '4'. t = 6 Simplifying t = 6
| X-13x^1/2-2=0 | | 0.2(d-6)=0.3d+5+0.1d | | 8x=9x-15 | | 2=x-26 | | liny=2t+4 | | -10x^2+15=0 | | x^2-2x=3-4 | | 54-5x=9-10x | | -0.7-0.6=0.2y+3.4 | | 2y-6y=18 | | 5r-7s+8r-11s= | | 4x^2+12x+3= | | F=W-wrt | | 43-4x=13-10x | | 3x^3-x^4= | | -2-y=-8 | | 8(4x-8)=4(8x+7) | | log(x-3)+log(x-1)=log(3x-7) | | x(x+9)=4x+6 | | 40x^2-23x-30= | | -3(-7v+3)+8v=5v-r | | 8(2q-4)+5(q+11)=65 | | 24x^2+2x-15= | | 8y-7(1)+3=-4(1)+5y-9 | | x=50-(10/3)y | | (7x+8)+(x-22)=2 | | 2x=5x-180 | | 5x^2=11x+36 | | 3b-0.9=4b | | 4cos^4x-5cos^2x+1=0 | | -8y+8=-80 | | 81+99.4= |